Da informação à formação para a autonomia: o olhar do adolescente sobre a prevenção das DST/AIDS - Elen Soraia de Menezes (2007)
This study came out from my experience as a nurse in the Public Health Services. Besides that, I was provoked by the Programa Educacional Afetivo Sexual- PEAS and by the daily activities with the adolescents in the Escola Estadual Dona Diva de Oliveira, where I worked as a volunteer. So, with the objective to understand the sense the adolescents attribute to the information about the DST/ AIDS, I went to meet them through this search, qualitative in character and phenomenologic in treatment. I asked them the directional question: Tell me which sense you give/attribute to the information about the DST/AIDS in your daily affective life? The fourteen statements obtained permitted, after several readings, the construction of two open categories and their respective sub-categories: being in the world with DST/aids, thinking about AIDS as suffering, disease and death; as well as, conscious prevention, considering the own acts; taking care to live better(cogitare-cogitatus), self consciousness, avoiding future sufferings; care of others: solicitude in sensitizing ( transmitting knowledge) and zeal. To understand what the adolescents live, I founded my analysis on existentialist philosophers, whose workers deal with liberty, body, care, suffering and death. I also based myself on education, health and nursery theorists ,as well as adolescence and sexuality researchers. The statements presented in this study might stimulate educators, parents and health workers to comprehend that it is necessary to look at the adolescent in an attentive,careful and holistic manner, mainly concerning to subjects such as: sexuality, health education, education as a way to form citizens free and conscious to do their own choices, dialectics, respect and ethics, stimulating their looking for new ways and partnerships for thishard work. Besides that, the present study denounces the urgency to implant and to implement programs which can take those subjects in account. This would make to understand the adolescents and the professionals that take part in their formation as people who deserve respect and acknowledgment.